2008
DOI: 10.1007/s10518-008-9077-2
|View full text |Cite
|
Sign up to set email alerts
|

Seismic fragility curves for greek bridges: methodology and case studies

Abstract: This study focusses on the estimation of seismic fragility curves for all common bridge types found in modern greek motorways. At first a classification scheme is developed in order to classify the existing bridges into a sufficient number of classes. A total of 11 representative bridge classes resulted, based on the type of piers, deck, and pier-to-deck connection. Then an analytical methodology for deriving fragility curves is proposed and applied to the representative bridge models. This procedure is based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 15 publications
1
58
0
12
Order By: Relevance
“…Bridge-specific fragility curves are calculated for each bridge (for the longitudinal and transverse direction separately) and the results are discussed, highlighting the importance of the bridge-specific approach in assessing a bridge inventory. The bridges of the inventory are initially classified into categories according to the classification scheme presented in [3] and summarised in Table 2. A code number is defined for each bridge according to the pier, deck and the pierto-deck connection type.…”
Section: Software Development For Bridge-specific Fragility Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Bridge-specific fragility curves are calculated for each bridge (for the longitudinal and transverse direction separately) and the results are discussed, highlighting the importance of the bridge-specific approach in assessing a bridge inventory. The bridges of the inventory are initially classified into categories according to the classification scheme presented in [3] and summarised in Table 2. A code number is defined for each bridge according to the pier, deck and the pierto-deck connection type.…”
Section: Software Development For Bridge-specific Fragility Analysismentioning
confidence: 99%
“…In this context, numerous methodologies have been developed for the seismic vulnerability assessment of bridges for different levels of seismic hazard using fragility curves; analytical [1][2][3] as well as empirical [4] procedures have been put forward. In most cases, bridges within a road network have different structural and geometric properties depending on the site topography, the selected structural system and construction method, and the foundation soil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both cases the correlation of capacity and demand is made using the capacity spectrum technique (capacity and demand plotted on the same diagram depicting spectral acceleration vs. spectral displacement of an equivalent SDOF system), which has been used for quite some time for buildings following the publication of the ATC-40 Manual (Council 1996). Figure 7.11 shows an example application of this procedure; the demand spectra can be either overdamped elastic spectra as suggested in ATC-40, or proper inelastic spectra as in the figure (Moschonas et al 2009). It is clear from the figure that the bridge capacity is represented by a single curve, while assessment can be carried out for multiple levels of seismic demand, which is an essential feature of PBD procedures.…”
Section: Brief Overview Of Available Assessment Proceduresmentioning
confidence: 99%
“…Such a classification is performed herein following the corresponding classification schemes of ATC-13 [1985], NBI [FHWA 1995], HAZUS [FEMA-NIBS 2004], and the work of Argyroudis et al [2003], Nielson & DesRoches [2007], and Moschonas et al [2009]. A comprehensive review of the state of the art on the subject can be found in and .…”
mentioning
confidence: 99%